2011
DOI: 10.1016/j.molcel.2011.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Switching Cdk2 On or Off with Small Molecules to Reveal Requirements in Human Cell Proliferation

Abstract: Summary Multiple cyclin-dependent kinases (CDKs) control eukaryotic cell division, but assigning specific functions to individual CDKs remains a challenge. During the mammalian cell cycle, Cdk2 forms active complexes before Cdk1, but lack of Cdk2 protein does not block cell-cycle progression. To detect requirements and define functions for Cdk2 activity in human cells when normal expression levels are preserved, and non-physiologic compensation by other CDKs is prevented, we replaced the wild-type kinase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(136 citation statements)
references
References 50 publications
8
128
0
Order By: Relevance
“…We found that in the absence of 1NM-PP1, HCT116-CDK2 AS cells exhibit a modest proliferation defect compared with WT HCT116 cells (Fig. 3A), which is consistent with what has been previously reported (21). On treatment with 1NM-PP1, we found that proliferation of HCT116-CDK2 AS cells was further decreased, whereas we saw no effect in the HCT116-CDK2 WT cells (Fig.…”
Section: As Cdk2 Forms Active Complexes In Vitro and Can Be Selectivelysupporting
confidence: 91%
See 3 more Smart Citations
“…We found that in the absence of 1NM-PP1, HCT116-CDK2 AS cells exhibit a modest proliferation defect compared with WT HCT116 cells (Fig. 3A), which is consistent with what has been previously reported (21). On treatment with 1NM-PP1, we found that proliferation of HCT116-CDK2 AS cells was further decreased, whereas we saw no effect in the HCT116-CDK2 WT cells (Fig.…”
Section: As Cdk2 Forms Active Complexes In Vitro and Can Be Selectivelysupporting
confidence: 91%
“…In this report, we use a chemical genetic approach in which we replace endogenous WT CDK2 (CDK2 WT ) in transformed mouse embryonic fibroblasts (MEFs) and human colon cancer cells with an analog-sensitive (AS) version that is mutated to allow for acute and selective inhibition using modified ATP analogs. This approach has been used recently to identify a distinct, nonredundant role of CDK2 in cellular proliferation of nontransformed cells (21). Here, we show that small-molecule inhibition of CDK2 also disrupts cellular growth of transformed MEFs and human colon cancer cells, defining a role for CDK2 in cellular proliferation under the control of oncogenic signaling.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…To uncover the possible role of CDK2 in regulating the nuclear level of AID, we took advantage of a cell line in which the wildtype CDK2 is replaced by an analog-sensitive molecule (CDK2AS) (25). CDK2AS is hypomorphic compared with the control RPEhTERT cells, and its activity can be restored or further inhibited by the adenine analogs 6-BAP or 3-MB-PP1, respectively.…”
Section: Cdk2 Regulates Nuclear Aid Levelsmentioning
confidence: 99%